Riscos de inundação das áreas urbanas de Aquidauana e Anastácio/MS - Eveline Terra Bezerra (2022)
The search for water has always characterized humanity, leading villages and communities to be inserted in spaces close to water resources, thus guaranteeing their survival. With the accelerated and unplanned process of urbanization, environmental problems came, often defined by the occupation of spring areas, such as valley bottoms, representing spaces of little or no permeability. Law 12,651/2012 - New Brazilian Forest Code - defines Permanent Preservation Area (APP) as a protected area, covered or not by native vegetation, with the environmental function of preserving water resources, landscape, geological stability and biodiversity , facilitate the gene flow of fauna and flora, protect the soil and ensure the well-being of human populations. The study area involves the urban perimeters of the municipalities of Aquidauana and Anastácio, which according to the IBGE (Brazilian Institute of Geography and Statistics) form an urban center with an estimated population of 73,006 inhabitants and are located at a distance of about 140 km from Campo Grande, the capital of the state of Mato Grosso do Sul. The objective of the proposal is to map and analyze the APPs of the urban perimeters of Aquidauana and Anastácio/MS, pointing out the risk of flooding and vulnerability of the areas. The method adopted is the hypothetical-deductive, and the origin of the research came from the verification of the problems in the cities of Aquidauana and Anastácio, related to the floods caused by the floods of the watercourses, as well as the damages generated to the environment and to the urban environment. High resolution aerial images (Bing Maps) were used for the elaboration of the land use map, while the elaboration of the APPs map considered Law 12.651/2012 - New Brazilian Forest Code, involving springs, lakes and ponds, and water courses in the urban perimeters of the municipalities of Aquidauana and Anastácio. As for the results, 6.36 km² of minimum APPs were recorded in the study area, corresponding to 11.41% of the urban perimeter, also indicating data from the (CPRM) that show the high risk of flooding on the banks of the Aquidauana River.